Impact of Workplace Diversity Management on Employee Commitment in Nigerian Regulatory Agencies: A Theoretical Framework - Uchechi Chinazom Ekejiuba; Hauwa Lamino Abubakar; Frank Alaba Ogedengbe (Business, Management and Economics: Research Progress Vol. 2, 2024)
Every company desires to make a profit, and the only way to make that happen is to satisfy customers and get them to pay for products and services. The uneven implementation of Workplace Diversity Management laws across countries is a global concern. The potential for bias is increased when there is unequal treatment of all employees regardless of background, gender, ethnicity, race, social status, etc. This study focuses on the Nigerian regulatory agencies and looks at how different academics have interpreted the impact of workplace diversity management on employee engagement. The relationship between the significant variables was examined using the constructs of inclusion, fairness, equal opportunity, policies and programs, leadership style, and the moderating effect of organizational support. Additionally, a theoretical framework methodology was applied, emphasizing two theories (Salad Bowl and Thomas and Ely’s perspectives) that served as the foundation for the investigation after a thorough review of several pertinent literature sources from reputable journals. To ensure currency, however, only studies that were released in the previous five years were included in this analysis. Using keywords from the independent and dependent variables, as well as their corresponding proxies, one hundred and thirty-one (131) pertinent bodies of literature from respectable journals were consulted and included to find theories that were used. The findings revealed that these theories were best fit for multicultural nations like Nigeria as they were adopted by private and public sector organizations in India, Indonesia, and the United States which are rich in diversity. The findings revealed that Nigerian public agencies lack effective implementation of diversity management policies and are therefore encouraged to embrace diversity, absorb minorities where applicable, and leverage the variety. By encouraging unity in diversity and recognizing individual differences, employees’ commitment will increase which will result in loyalty. Organizations are therefore advised to embrace diversity, absorb minorities where necessary, and leverage variety.